2016
DOI: 10.1161/hypertensionaha.115.06794
|View full text |Cite
|
Sign up to set email alerts
|

Renal Denervation Improves Exaggerated Sympathoexcitation in Rats With Heart Failure

Abstract: Renal denervation (RDN) has been postulated to reduce sympathetic drive during heart failure (HF), but the central mechanisms are not completely understood. The purpose of the present study was to assess the contribution of neuronal nitric oxide synthase (nNOS) within the paraventricular nucleus (PVN) in modulating sympathetic outflow in rats with HF that underwent RDN. HF was induced in rats by ligation of the left coronary artery. Four weeks after surgery, bilateral RDN was performed. Rats with HF had an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 79 publications
3
36
0
Order By: Relevance
“…Thus, recognizing the contribution of HIF-1α and NMDA receptors represent some new potential therapeutic targets for future clinical interventions to appropriately reduce sympathoexcitation without the detrimental effects. These results provide the insight into the possible underlying mechanisms that result in the beneficial effects of both ExT and RDN 19, 58 .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, recognizing the contribution of HIF-1α and NMDA receptors represent some new potential therapeutic targets for future clinical interventions to appropriately reduce sympathoexcitation without the detrimental effects. These results provide the insight into the possible underlying mechanisms that result in the beneficial effects of both ExT and RDN 19, 58 .…”
Section: Discussionmentioning
confidence: 82%
“…Our previous work has identified the PVN and specifically the imbalance between the excitatory glutamatergic and inhibitory NO mechanisms within this site to lead to detrimental sympathoexcitation in HF 6, 53, 55 . Further, our recent studies have utilized the efficacy of ExT (4,5,6) 19, 56, 57 and RDN 58 to reduce sympathoexcitatory drive (interestingly appropriately without the adverse effects such as those observed in the MOXCON trial) to examine the changes in central mechanisms specifically within the PVN to identify a potential therapeutic target. Thus, recognizing the contribution of HIF-1α and NMDA receptors represent some new potential therapeutic targets for future clinical interventions to appropriately reduce sympathoexcitation without the detrimental effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that ARN stimulation activates RVLM projecting PVN neurons (Xu et al, 2015). Stimulation of ARN also increases sympathetic activity and arterial pressure (Patel et al, 1986; Patel et al, 2016; Xu et al, 2015). Afferent information from the kidney may play an important role in the coordination of neural and humeral activation, concerned with body fluid balance and the regulation of arterial blood pressure in normal and disease conditions such as chronic heart failure (CHF) and hypertension (Caverson et al, 1988; Ciriello et al, 1987; Day et al, 1987; Kopp, 2015; Patel et al, 2016; Solano-Flores et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an enhanced afferent renal input to the PVN is shown to be intimately involved in processes leading to sympathoexcitation in the CHF condition (Patel et al, 2016; Xu et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation